Care Stick dan Core Paddle: Media Pembelajaran Pendidikan Jasmani Adaptif Untuk Siswa Disabilitas - Fajar Hidayatullah; Khoirul Anwar; Ruski (UIR Press, 2020)
The development of this sports learning media in the form of a relay baton and table tennis bat to solve the problem of motion learning for students at State Special School Keleyen. It is safe learning media because it will be used by students who are often hyperactive, it is comfortable to use for students with physical disabilities and to attract students’ attention with students’ uniqueness. The development research method uses a descriptive quantitative approach applied with adjustments to the COVID-19 pandemic condition so that numbers of samples do not enable with large amount and are made separately to maintain the health and safety of all related parties in it. The sampling technique uses purposive sampling with details of a total of 60 samples divided in 3 development stages and descriptive analysis is conducted to conclude the development result. The research results shows the form of a relay stick with the safe characteristics, it is comfortable to use and attracting attention have been reached supported by the majority of respondents that give positive responses to the results of the development of the CARE Stick can be accepted well as a modified relay stick based on the needs of Keleyan Special School students. Likewise, the CORE Paddle is as a modification of table tennis bat that can be accepted well as a result of development that can fulfill the needs of Keleyan State School students.